(untitled) (Raíces: Revista de Ciencias Sociales y Políticas, 2021)
This research was developed in the city of Masaya- Nicaragua, the cradle of Nicaraguan folklore, which has manifestations of material and spiritual culture among those who manifest themselves, economic life, social relationships, art, music, dance among others. The objective of the research is the search for the identity of the population according to the dance practices of the population, in the specific case of the black dance, being a cultural manifestation of the town of Monimbó of the city of Masaya, which is personified in honor of the patron saint festivities of San Jerónimo. The purpose of this research was born with the curiosity to know What is the black dance? the original characteristics they represent, the transformations and processes of change that the dance has undergone. Thus allowing the approach to the appropriation, transmission and projection of the cultural historical process of the origin of the black dance in the city of Masaya.